The Effect Of Caf Menu Variations And Atmosphere On Competitive Advantage (Case Study on Volkswagen Café in Tasikmalaya) - Andri Esa Permana; Rita Tri Yusnita; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of menu variations and cafe atmosphere on competitive advantage (a case study on Volkswagen Café in Tasikmalaya). The method used in this study is causality through a survey approach. With a research sample of 100 consumers of Volkswagen Café in Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the menu variation has a very good rating classification, the cafe atmosphere has a good rating classification, while the competitive advantage has a very good rating classification for Volkswagen Café Consumers in Tasikmalaya. Simultaneously, menu variations and cafe atmosphere have a significant influence on competitive advantage. Partially, menu variations have a significant effect on competitive advantage and cafe atmosphere has a significant influence on Volkswagen Café's competitive advantage in Tasikmalaya.